Sistem Informasi Administrasi Berbasis Web Pada Bengkel Mesin H&S Tegal - Fanny Fatma Wati; Andrian Eko Widodo; Nurlaelatul Maulidah; Suleman; Ratna Kurnia Sari (KALBISCIENTIA Jurnal Sains dan Teknologi, 2023)
H&S Machine Shop is a service company that handles the repair of motorcycle, diesel, and automobile engines. The implementation of administrative activities still applies a manual system ranging from notes, cash books, inventory of goods, to reports still carried out by handwriting.In addition to being inefficient because it increases the use of paper, in the process of recording and processing data there is often human error, inaccurate reports made, and delays in finding certain data when needed, so it requires more time and energy. Therefore, the right solution is needed to overcome these problems, namely by designing a computerized system. The data collection methods used are observation, interviews, and literature studies. The software development method used is the waterfall method. The result of this study is to help administrative work become more effective and efficient in supporting activities in the H & S Machine Workshop